Cac40 أثر حوكمة الشركات على القيمة السوقية للمؤسسات الاقتصادية: دراسة قياسية لعينة من شركات مؤشر - قدام جمال; بودرمين سارة (جامعة الوادي University of Eloued, 2024)
This study aimed to examine the impact of corporate governance on the market value of firms, using a sample of 12 French companies listed on the CAC40 index during the period 2015-2022. To achieve the study's objective, panel data (cross-sectional time series) was employed. The study found a statistically significant positive impact of institutional ownership, concentrated ownership, gender diversity on the board, and foreign board members on the market value of firms, as represented by the market price of the stock. The results also indicated a statistically significant positive effect of the control variable, earnings per share, while agency cost and asset growth rate had no effect on the market price of the stock.
The Impact of Corporate Governance on the Market Value of Economic Firms: An Econometric Study of a Sample of CAC40 Index Companies
Keywords: حوكمة الشركات; مجلس الإدارة; هيكل الملكية; السعر السوقي للسهم; نماذج البانل